Systematic review and two new cases of primary upper urinary tract neuroendocrine carcinomas. (2018) - Nakasato, Takehiko; Hiramatsu, Aya; Matsui, Yuki; Unoki, Tsutomu; Shimoyama, Hideaki; Oshinomi, Kazuhiko; Morita, Jun; Maeda, Yoshiko; Naoe, Michio; Fuji, Kohzo; Ogura, Hiroshi; Homma, Mayumi; et al.
Abstract: Background: Upper urinary tract neuroendocrine carcinoma (UUT-NEC) is extremely rare and has a poor prognosis. Although a few cases of successful treatment have been reported, no treatment has shown established efficacy. Patients and methods: We analyzed 70 UUT-NEC patients, including 68 with small cell neuroendocrine carcinoma (SCNEC) and large cell neuroendocrine carcinoma (LCNEC) reported between 1985 and 2017 and 2 treated at our hospital. Results: Median patient age was 66 years, 58.6% were men, and 60% were of Asian descent. Most UUT-NECs were SCNEC (68; 95.7%), whereas LCNEC was very rare (2; 2.9%). More than half of the patients had accompanying other histological components, the most common being urothelial carcinoma (51.5%), whereas 41.4% had NEC alone. Of the 70 patients, 27 underwent additional therapy (e.g., chemotherapy and radiotherapy) along with surgery. Median survival was 15 months. In univariate analysis, stages T1–2 disease showed better prognosis than stages T3–4 ( P   <  0.001). Additional treatment (e.g., chemotherapy and radiotherapy) significantly improved prognosis ( P  = 0.014). Moreover, platinum-based chemotherapy also was associated with improved prognosis ( P  = 0.017). For platinum-based chemotherapy, multicollinearity with additional treatments was strong, and, thus, these data were not included in the analysis. Multivariate analysis revealed pathological stage (T1–2 vs. T3–4; P  = 0.003) and additional treatment ( P  = 0.028) to be independent predictors of improved prognosis. Conclusion: Although UUT-NEC has a poor prognosis, additional treatment along with surgery and therapeutic intervention and stage T1–2 disease are independent factors to improve prognosis.